Crossing boundaries: developing preservice teachers' professional identity through hybrid school-university partnerships - Stephanie Buelow (Emerald Publishing, 2024)
Purpose - School-university partnerships are the core of effective teacher preparation programs, and central to this model are the classroom teachers who mentor preservice teachers into the profession. This article describes an innovative collaboration that transcends institutional boundaries, operating in a hybrid space, aimed at supporting preservice teachers' development as educators, expanding their professional networks and fostering their sense of belonging and professional identity within a broader community of teacher leaders. Design/methodology/approach - This article describes a hybrid partnership model that provides preservice teachers with innovative mentoring experiences. Research on hybrid partnership models and boundary-spanning frames the discussion. The article provides a brief overview of two iterations of a collaboration between elementary preservice teachers and a cohort of teacher leaders in a fellowship program. The paper concludes by discussing lessons learned and directions for future research on the topic. Findings - Preservice teachers benefit from opportunities to engage with a variety of mentors throughout their program. While the classroom teacher serving as a mentor is central to teacher preparation, there is a space for hybrid partnership models that provide preservice teachers additional mentors to support their development and connections to a professional learning community of teacher leaders. Through innovative hybrid collaborations, preservice teachers engage with diverse mentors, expanding their professional networks and preparing them to navigate the complexities of the educational landscape with a sense of belonging and identity. Originality/value - This article contributes to the literature on hybrid partnership models, aimed at empowering preservice teachers by integrating them into a professional community of teacher leaders, fostering their sense of belonging, identity and preparedness to navigate the complexities of the profession.